Miejsce standardu burgenlandzkochorwackiego wśród języków indoeuropejskich - Ślęzak, Artur (Slavia Centralis, 2020)
The place of the standard language of Burgenland Croats among the Indo-European languages The language of Burgenland Croats was based on Croatian dialects from the 15 to 17th centuries. Native speakers of the standard use three dialects of the Croatian language, mainly Shtokavian and Chakavian, and Kajkavian, in which there are preserved many archaisms and neologisms. The standard of Burgenland Croats was included in the grammar published in Eisenstadt (Gradišćanskohrvatska gramatika, 2003).